2011
DOI: 10.1088/1741-2560/8/1/016002
|View full text |Cite
|
Sign up to set email alerts
|

State-space decoding of primary afferent neuron firing rates

Abstract: Kinematic state feedback is important for neuroprostheses to generate stable and adaptive movements of an extremity. State information, represented in the firing rates of populations of primary afferent neurons, can be recorded at the level of the dorsal root ganglia (DRG). Previous work in cats showed the feasibility of using DRG recordings to predict the kinematic state of the hind limb using reverse regression. Although accurate decoding results were attained, reverse regression does not make efficient use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 37 publications
(94 reference statements)
0
32
0
Order By: Relevance
“…The bulk of these studies record firing rates from the afferent fibers [11], [12], [13], [14]. Yet since there are different afferent substrates for sensation of kinematics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The bulk of these studies record firing rates from the afferent fibers [11], [12], [13], [14]. Yet since there are different afferent substrates for sensation of kinematics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear characteristics of bladder units (Fig. 5) suggest that the inclusion of bladder pressure velocities (contraction, relaxation) and the use of splines and other advanced regression techniques [13] may improve model accuracy. This approach can also be integrated with a contraction detection algorithm and closed loop stimulation for bladder control while optimizing the firing rate kernel.…”
Section: Discussionmentioning
confidence: 99%
“…5). Some decoding algorithms, such as state-space regression models, have demonstrated significant improvements over reverse regression models but are not currently tractable in real-time [10]. Other decoding methods, such as Bayesian classifiers or fuzzy neural networks may achieve similar improvements while remaining computationally tractable [11].…”
Section: Discussionmentioning
confidence: 99%
“…Access to this sensory information at a single location is a significant benefit over recording from multiple peripheral nerve locations or with multiple external sensors. Recent studies have demonstrated that limb position and velocity can be decoded from signals recorded from lumbar DRG in cats [9], [10]. …”
Section: Introductionmentioning
confidence: 99%